2021
DOI: 10.1177/23259671211015616
|View full text |Cite
|
Sign up to set email alerts
|

Independent Versus Transtibial Drilling in Anterior Cruciate Ligament Reconstruction: A Meta-analysis With Meta-regression

Abstract: Background: Anterior cruciate ligament (ACL) reconstruction can be performed with different techniques for independent and transtibial (TT) drilling of femoral tunnels, but there is still no consensus on which approach leads to the best outcome. Purpose: To assess whether the independent or TT drilling approach for ACL reconstruction leads to the best functional outcomes. Study Design: Systematic review; Level of evidence, 2. Methods: A systematic literature search was conducted on July 1, 2020, using the PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
2
13
0
4
Order By: Relevance
“…These results underline recent systematic reviews comparing transtibial and independent femoral drilling in ACL reconstruction in adult patients who also found no significant difference in re-injury rate between the two techniques [14,38]. However, these systematic reviews showed that independent femoral drilling led to reduced instrumentally measurable anterior tibial translation, a lower rate of positive postoperative pivot-shift test findings, and higher patient reported outcome measures (PROMs) such as IKDC subjective score or Lysholm score [14,38]. Another systematic review could reveal that the rate of post-traumatic osteoarthritis is significantly lower after anatomic ACL reconstruction compared to non-anatomical techniques [12].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results underline recent systematic reviews comparing transtibial and independent femoral drilling in ACL reconstruction in adult patients who also found no significant difference in re-injury rate between the two techniques [14,38]. However, these systematic reviews showed that independent femoral drilling led to reduced instrumentally measurable anterior tibial translation, a lower rate of positive postoperative pivot-shift test findings, and higher patient reported outcome measures (PROMs) such as IKDC subjective score or Lysholm score [14,38]. Another systematic review could reveal that the rate of post-traumatic osteoarthritis is significantly lower after anatomic ACL reconstruction compared to non-anatomical techniques [12].…”
Section: Discussionsupporting
confidence: 83%
“…The independent drilling technique is considered a key feature of anatomical ACL reconstruction, since the femoral insertion zone of the ACL can be better reached via the medial portal than via the tibial tunnel [ 9 , 10 ]. The most commonly used independent drilling technique is the medial portal drilling technique [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta‐analysis compared transtibial (TT) drilling method and independent methods in terms of outcomes and complications [8]. Independent femoral tunnel drilling provided better results than the TT approach, although the difference was not clinically significant Amongst the independent drilling options, the anteromedial portal technique seemed to provide the most favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of between-study heterogeneity, prediction intervals are wider than confidence intervals, and therefore, study conclusions may differ if based on the prediction interval rather than the confidence interval [12]. For example, a confidence interval shows a "significant" benefit to employing a treatment that does not include zero, whereas the wider prediction interval is more uncertain and does include zero (see Figure 1; replicated from Figure 4, subgroup 1.5.1 in [14]). It is reasonable to assume that meta-analysis prediction intervals are overlooked in sports medicine research in a similar way to medicine [11,15].…”
Section: Introductionmentioning
confidence: 99%